Physiological responses of speed skaters to treadmill low walking and cycle ergometry - Rundell, K. W.; Pripstein, L. P. (International Journal of Sports Medicine, 1995)
Speed skaters have previously relied on cycle ergometry for physiological testing. Current evidence suggests skate-specific testing might be more appropriate. Unlike cycling, skating and off-ice low walk training involves a 'crouched' posture, placing the quadriceps in static contraction. This may compromise blood flow to working muscles and influence VO2. We compared physiological variables between skate-specific treadmill low walking (LW) and cycle ergometry (BK). Skaters (N = 8) performed LW and BK to fatigue in randomized order. No difference existed for peak HR. Peak VO2 was lower for LW (4.13 +/- 0.34 vs 4.43 +/- 0.35, p < 0.05). Peak VE was lower during LW (146 +/- 13 vs 180 +/- 31, p < 0.05). R was significantly lower for LW, although no difference in peak lactate (LA) was evident. At submaximal heart rates, VO2 was lower during LW (p < 0.05), and submaximal LA was higher when expressed as percent peak VO2 (p < 0.05). These results are consistent with the hypothesis that skating posture limits O2 delivery to the lower extremities, and thus accounts for a greater dependence upon anaerobic energy production.